Ecological biochemistry: (Wiley-VCH Verlag GmbH & Co., 2015)
Ecological biochemistry refers to the interaction of organisms with their abiotic environment and other organisms by chemical means. Biotic and abiotic factors determine the biochemical flexibility of organisms, which otherwise easily adapt to environmental changes by altering their metabolism. Sessile plants, in particular, have evolved intricate biochemical response mechanisms to fit into a changing environment. This book covers the chemistry behind these interactions, bottom up from the atomic to the system's level.